Do Anti‐immigration Parties Matter? The Case of the Sweden Democrats and Local Refugee Policy. (16th June 2014) - Bolin, Niklas; Lidén, Gustav; Nyhlén, Jon
<x xml:space="preserve">Abstract</x> With the increased electoral success of anti‐immigration parties, questions regarding what impact the parties actually have naturally follow. Previous research has rarely explored this question. Furthermore, within this body of research, one is given different answers. While some argue that anti‐immigration parties have made an impact on public policy, others find no such evidence. This article shows that some of this inconsistency is a consequence of the methodological strategies that have been employed. Previous studies are either single case studies or comparisons of a small number of countries. Consequently, different parties in different institutional settings are compared, making it difficult to estimate the actual impact of the party of interest. In order to circumvent such methodological problems, this article explores the question of anti‐immigration party impact on a local level and asks if the Sweden Democrats (SD) have managed to influence decisions on refugee reception in Swedish municipalities. The analysis shows mixed results. First, while unable to find an independent effect of the size of the representation of the SD, it appears that the party's impact is conditioned by them holding the balance of power. Second, the SD's impact is not dependent upon whether there is right‐wing or left‐wing rule, although local migration policy is stricter when the main right‐wing party has strong support.